Analysis of InGaN-Delta-InN Quantum Wells on InGaN Substrates for Red Light Emitting Diodes and Lasers - Bryan Melanson; Cheng Liu; Jing Zhang (IEEE Photonics Journal, 2021)
Modern multi-color RGB micro-light emitting diode (μLED) displays and digital micro-mirror laser projectors often require the use of both III-V and III-Nitride material systems for different pixel/laser colors. This is due primarily to the conventionally low efficiencies of red emitters based on the InGaN materials system, which is used to create green and blue emitters for RGB displays. The main challenges for InGaN red emitters are the quantum confined stark effect (QCSE) and the difficulty of incorporating high In-content into the active region. In this work, InGaN/InGaN/delta-InN quantum wells (QWs) on InGaN substrates are proposed and demonstrated to show significant enhancement in electron-hole wavefunction overlap (Γe_hh) and spontaneous emission radiative recombination rate (Rsp) in the red emission regime. Analysis of InGaN/InGaN/delta-InN QWs with InGaN barriers emitting at 630 nm was performed using a self-consistent six-band $k · p$ formalism. The Γe_hh was shown to increase by more than 230% compared to an InGaN/InGaN QW emitting at 630 nm, leading to significant increases in Rsp and internal quantum efficiency (ηIQE). With growth of InN monolayers on InGaN now readily achievable, this novel active region design could pave the way for high-efficiency, native red-emitting InGaN LEDs and lasers.